Association between menopausal symptoms and relationship distress. (December 2019) - Kling, Juliana M.; Kelly, Megan; Rullo, Jordan; Kapoor, Ekta; Kuhle, Carol L.; Vegunta, Suneela; Mara, Kristin C.; Faubion, Stephanie S.
Highlights: Associations between menopausal symptoms and relationship distress were identified. Absence of relationship distress was associated with less severe menopausal symptoms. The relationship persisted for total and psychological domains in full analyses. Addressing psychosocial factors may prove useful for menopausal women. Abstract: Objective: To determine the association between relationship distress and menopausal symptoms. Study design: A retrospective analysis was conducted of questionnaires completed by women 40–65 years of age seeking menopause or sexual health consultation between May, 2015 and May, 2017. Main outcome measures: Associations between menopausal symptoms assessed using the Menopause Rating Scale (MRS) and relationship distress measured on the Kansas Marital Satisfaction Scale (KMSS) were evaluated with two-sample t-tests. Linear regression was used to assess associations after adjusting for potential confounders. Results: The sample of 1884 women averaged 53 years of age (SD = 6.1); most were white (95%), employed (66%), married (90%), and well-educated (≥ college graduate, 64%). Women reporting no relationship distress (KMSS ≥ 17) had less severe menopausal symptoms overall compared with women reporting relationship distress (total MRS score 13.1 vs 16.0, P < 0.001), with similar findings in each MRS domain. In multivariable analyses, this relationship persisted for total MRS scores and for psychological symptoms among women with no relationship distress, who scored an estimated 1.15 points (95% CI 0.52–1.78) lower on the total MRS and 0.82 points (95% CI 0.53–1.10) lower in the psychological symptom. Conclusions: The absence of relationship distress was associated with less severe menopausal symptoms, particularly in the psychological domain, in women presenting to a women's health clinic. Given the cross = sectional design, the direction of the relationship is unknown.